Postmemory Interpretations of Second World War Love Affairs in Twenty-First-Century Norwegian Literature - Unni Langås (Humanities)
Love and intimate relations between German men and Norwegian women were a widespread phenomenon during WWII. Like in many other European countries, these women were stigmatized and humiliated both by the authorities and by the civilian population. In this article, I discuss four postmemory literary works that address this issue: Edvard Hoem’s novel Mors og fars historie (The Story of My Mother and Father, 2005), Lene Ask’s graphic novel Hitler, Jesus og farfar (Hitler, Jesus, and Grandfather, 2006), Randi Crott and Lillian Crott Berthung’s autobiography Ikke si det til noen! (Don’t tell anyone!, 2013), and Atle Næss’s novel Blindgjengere (Duds, 2019). I explore how the narratives create a living connection between then and now and how they deal with unresolved questions and knowledge gaps. Furthermore, I discuss common themes such as the fate and identity of war children, national responsibilities versus individual choice, and norms connected to gender and sexuality. I argue that these postmemory interpretations of wartime love affairs not only aim to retell the past but to investigate the normative frameworks within which these relationships took place. My contention is that the postmemory gaze pays primary attention to the power of cultural constructions—of nationality, identity, and gender—as well as their context-related historical changes.